Pendampingan anak yang memiliki kesulitan belajar “Disleksia’’ di Sekolah - Dewi Rosmawati; Y. Touvan Juni Samodra (JPPTK: Jurnal Pendidikan Pembelajaran & Penelitian Tindakan, 2021)
SD Negeri 21 Jopo located in Jopo hamlet, Cupang Gading village, Sekadau upstream district, Sekadau district, 39 students, among the number of students, needs exceptional guidance. The student named Satria (12 years old) was born without a father, has a natural skin feature all over his body which is genetically from his mother, so his friends often shun his friends. Physically, he may not be too different from other students. However, physically he becomes a hyperactive person, cannot stay still, and cannot focus on learning activities, so he is far behind the lessons of his other friends. The best practice aimed to provide educational services to these students, even if only one person. The method used is by conducting special guidance activities for these students with a "Humanistic" approach to humanizing humans, assuming all humans are the same regardless of their physical or physical differences. The implementation of activities is carried out in two events, first with fun learning and understanding positive perceptions of classmates. Second, special guidance is held after school hours so that students (Satrio) get more service. As a result, Satrio is now in grade 3 and can socialize with friends at school. Even though the grades results cannot exceed other friends, Satrio is still eager to learn to have a good heart, high enthusiasm to continue to school, be the most diligent in every school cleaning activity, and be a source of inspiration for teachers and peers.